Coagulopathies and pediatric stroke - Rajpurkar, Madhvi; Lusher, Jeanne M. (Journal of Pediatric Neurology, 2010)
Pediatric stroke is a heterogeneous disorder and is associated with significant morbidity and mortality in children. The role of thrombophilia is becoming increasingly important in the pathogenesis of stroke but its effect on clinical outcome and recurrence is not yet well defined. This review provides a summary of current knowledge of thrombophilia in pediatric stroke.
Keywords: Pediatric stroke; coagulation abnormalities; thrombophilia